Human avatar in virtual environment / Shaiful Baharie Mohd Ali - Shaiful Baharie, Mohd Ali (2004)
The name of this project is Human Avatar in Virtual Environment. This system consists of two subsystem, the interface for this system and the controls. Interface function as an introductory page and provides navigation buttons that will guide user to interact with it. This control is part that involved in human control and how it should act with environment. The Internet had become an important medium of communication today. Since then, the world had seen the evolution of information representation. We had made the journey form ID ((in the days of DOS) to 20 and now we are crossing the threshold into an inevitable world where 3D graphics on the computer serve as our interface and our medium of choice for data communication. The use of 3D on the Web allows virtually infinite amount of interactivity. The most important achievement of 3D technology is the making of3D simulation, which provides interaction with the user in 3D graphic that look exactly like real. The Human Avatar applies the concept of imulation by creating 3D objects like object in the real world. It emphasizes on the user interactivity where user can interact with the simulation and learn through 3D environment. The Human Avatar concerns the use of simulation as a mean of learning something and shows to the user what they can see in real world. Creating 3D graphics of the environment. In another word, a realistic-looking process is presented on the computer screen. This report provides an overview of the project development. It is also contains the introduction to the conception of the project the Scope and boundaries covered by the simulation, the phases of the system analysis and development processes and the system design. It also contains the system implementation, testing anda evaluation.